The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1151-2916.1986.tb04722.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and Transport of NiO Cathodes in Molten Carbonate Fuel Cells

Abstract: Equilibrium NiO solubility measurements were made inLi2C03/K2C03 mixtures as a function of temperature, ambient gas environment, and salt composition for gases containing 3.1% HzO. The equilibrium solubility was found to increase with increasing temperature, COz partial pressure, and cation fraction Li+ and to decrease slightly with increasing O2 partial pressure. These results were coupled with theoretical predictions of (1) 02, H2, and C 0 2 activities and (2) compositional gradients which develop across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Although no consistent discrete location is present at which nickel deposition occurs, higher concentrations are frequently found to occur in the central region of the matrix (3,8,16,17). Reference (17) contains micrographs of nickel deposited in the matrix obtained by both scanning electron microscopy and energy dispersive x-ray spectroscopy.…”
Section: Application Of the Continuity Equation To The Matrix-mentioning
confidence: 96%
See 2 more Smart Citations
“…Although no consistent discrete location is present at which nickel deposition occurs, higher concentrations are frequently found to occur in the central region of the matrix (3,8,16,17). Reference (17) contains micrographs of nickel deposited in the matrix obtained by both scanning electron microscopy and energy dispersive x-ray spectroscopy.…”
Section: Application Of the Continuity Equation To The Matrix-mentioning
confidence: 96%
“…EIS has proven to be a powerful tool to obtain system specific parameters of coatings, especially for evaluating the early deviation of organic coatings from their initial capacitive behavior (1)(2)(3)(4). An excellent paper by Kendig and Scully on this subject exists (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in practice, the formed Ni> ions can diffuse, through the matrix structure, towards the anode where the reducing conditions enhance the precipitation of metallic Ni particles. This kind of 'driving force' does not allow the system to reach its solubility equilibrium and thus the dissolution process of the cathode structure becomes continuous (Baumgartner, 1986;ESC, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Theses structural changes of the cathode caused by the reduction give challenges. [6][7][8] Two types of dissolution mechanism of NiO (acidic or basic dissolution) have been proposed and it is reported that the solubility of NiO depends on the acid-base properties of the molten carbonate or carbonate mixture. 9 In order to solve the problem of NiO dissolution, many investigators have studied alternative electrolytes and cathodes.…”
Section: Introductionmentioning
confidence: 99%